2019
DOI: 10.1590/1980-5373-mr-2017-0969
|View full text |Cite
|
Sign up to set email alerts
|

Intercritical Heat Treatment Temperature Dependence of Mechanical Properties and Corrosion Resistance of Dual Phase Steel

Abstract: This study investigated the effect of intercritical heat treatment temperature on the tensile properties, work hardening and corrosion resistance of dual phase steel. Ferrite-martensite dual phase steel with different martensite volume fractions were obtained after heat treatment at different intercritical temperatures. Microstructure, mechanical properties of steel were measured and the corrosion resistance was evaluated via polarization test. Tensile strength of the specimens increased by increasing the mart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This is because of the weaker galvanic couple between ferrite and martensite compared to that between ferrite and pearlite. In addition, an increasing volume fraction of martensite increases the corrosion rate [11]. The previous results are supported in reference [22] where similar behavior was found for different DP steels in a solution containing chloride ions.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is because of the weaker galvanic couple between ferrite and martensite compared to that between ferrite and pearlite. In addition, an increasing volume fraction of martensite increases the corrosion rate [11]. The previous results are supported in reference [22] where similar behavior was found for different DP steels in a solution containing chloride ions.…”
Section: Introductionsupporting
confidence: 83%
“…In addition, it has been reported that the dual-phase steel tempered at higher temperature of 800 • C (martensite island morphology in the ferrite matrix), had better corrosion resistance properties than the dual-phase steel tempered at lower temperature of 730 • C, which consists of fibrous ferrite and martensite [10]. Abedini et al [11] mentioned that an increase in martensite amount does not favor the corrosion rate of DP steels. However, DP steel exhibited high corrosion resistance compared to ferrite-pearlite steel, due to the fact that the galvanic couple between ferrite and martensite is weaker than that between ferrite and pearlite.…”
Section: Introductionmentioning
confidence: 99%
“…Dualphase (DP) steels have received massive consideration in the past few decades because of increased application in the automotive industry. When compared to conventional high strength low alloyed (HSLA) steels, DP steels display improved mechanical properties (Abedini et al 2019;Salamci et al 2017). Steels with DP structure have a place with a gathering of present-day multi-phase steels described by ferrite matrix containing at least one or more phases (martensite, bainite, and leftover austenite) (Abedini et al 2019;Gerengi et al 2020;Keleştemur et al 2009;Song et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to conventional high strength low alloyed (HSLA) steels, DP steels display improved mechanical properties (Abedini et al 2019;Salamci et al 2017). Steels with DP structure have a place with a gathering of present-day multi-phase steels described by ferrite matrix containing at least one or more phases (martensite, bainite, and leftover austenite) (Abedini et al 2019;Gerengi et al 2020;Keleştemur et al 2009;Song et al 2019). The concurrence of delicate/hard phases and their connection in working conditions permit both high strength and malleability to be accomplished.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation